Design of a polarization-independent, wide-angle, broadband visible absorber. Issue 2 (19th January 2018) - Jia, Xiuli; Wang, Xiaoou
Abstract: Many optical systems benefit from elements that can absorb a broad range of wavelengths over a wide range of angles, independent of polarization. In this paper, we present a polarization-independent, wide-angle, broadband absorber in the visible regime that exploits strong symmetric and asymmetric resonance modes of electromagnetic dipoles. It makes use of a bilayer cross-pattern structure which is simple, having five layers that include two stacks of metal ribbon in cross-patterns, two dielectric spacers and a metal reflecting layer. Simulations show that the design exhibits a significantly enhanced absorption property when compared to a device with a bilayer metal film structure or any other complex structure of cross-patterns that have no intersection angle. The maximum absorption efficiency of the device is 100% at resonances, and its absorption characteristics can be maintained over a wide range of angles of incidence – up to ± 60° – regardless of the incident polarization. This strategy can, in principle, be applied to other material systems and could be useful in diverse applications, including thermal emitters, photovoltaics and photodetectors.